Barbara Jordan and the ongoing struggle for voting rights. Issue 3 (2nd July 2020) - Woods, Carly S.
ABSTRACT: This essay examines the voting rights advocacy of Congress member Barbara C. Jordan. Drawing on some of Jordan's lesser known speeches, including an address commemorating the 75th anniversary of the nineteenth amendment and congressional testimony on the Voting Rights Act of 1975, I highlight how Jordan rhetorically refigured dominant understandings of the meaning of the vote based on gender, race, and ethnicity. Although she was certain to commemorate past suffrage successes, Jordan also contested and nuanced these notions, reminding her audiences that the quest for equitable voting rights was a long, ongoing, coalitional struggle.